No longer written : the use of conjectural emendation in the restoration of the text of the New Testament, the Epistle of James as a case study - Wettlaufer, Ryan Donald. (New Testament Tools, Studies and Documents, 2013)
This is an important time for textual criticism of the New Testament. A fundamental re-evaluation is underway of both the purpose of the discipline and the nature of the manuscripts upon which it relies. The place of the controversial method of conjectural emendation is a debate that encompasses both of these issues. In this study, Ryan Wettlaufer explores the theory and practice of the method and then, using the Epistle of James as a case study, argues that conjectural emendation is an important tool that can be used to restore readings which were once found in the original text but now are No Longer Written.